2012
DOI: 10.1007/s13364-012-0105-x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in feeding habits and diet selection by wild boars in a semi-arid environment of Argentina

Abstract: Your article is protected by copyright and all rights are held exclusively by Mammal Research Institute, Polish Academy of Sciences, Bia#owie#a, Poland. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your work, please use the accepted author's version for posting to your own website or your institution's repository. You may further deposit the accepted author's version on a funder's repository at a funder's request, provided it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
2
14
0
2
Order By: Relevance
“…In general, the increasing number of studies on fungal consumption by mammals has determined the diversity of items of the diet from stomach content analyses (e.g. Baubet et al, 2004;Vernes and Lebel, 2011), and only a few have used feces for this purpose (Carey et al, 1999;Vernes et al, 2001;Nouhra et al, 2005;Cuevas et al, 2013). In our study, a high frequency of spores from both hypogeous and epigeous fungi was detected in feces samples.…”
Section: Discussionsupporting
confidence: 52%
“…In general, the increasing number of studies on fungal consumption by mammals has determined the diversity of items of the diet from stomach content analyses (e.g. Baubet et al, 2004;Vernes and Lebel, 2011), and only a few have used feces for this purpose (Carey et al, 1999;Vernes et al, 2001;Nouhra et al, 2005;Cuevas et al, 2013). In our study, a high frequency of spores from both hypogeous and epigeous fungi was detected in feces samples.…”
Section: Discussionsupporting
confidence: 52%
“…This herbaceous class is maintained by grazing pressure (e.g., native grasses intensively grazed by cattle, exotic pastures, grasslands with very small earthmounds and bare soil areas). The intensive use of grasslands and pastures had already been described in southern Pantanal and in other regions ( Barrett, 1982 ; Baubet, Bonenfant & Brandt, 2004 ; Choquenot & Ruscoe, 2003 ; Desbiez et al, 2009 ; Dexter, 1998 ; Dexter, 1999 ; Graves, 1984 ; Oliveira-Santos, 2013 ), and plants like grass, herbs and forbs usually represent a considerable part of the feral pigs and wild boar diets ( Baber & Coblentz, 1986 ; Cuevas et al, 2013a ; Cuevas, Ojeda & Jaksic, 2013b ; Giménez-Anaya et al, 2008 ; Hellgren, 1993 ; Taylor & Hellgren, 1997 ). Furthermore, the SDM approach showed that habitats with greater suitability for feral pigs are those predominantly herbaceous (around 80% coverage), interspersed with patches of seasonally dry forest (optimum between 35 and 40% coverage) and not too far from water bodies (around one kilometer).…”
Section: Discussionmentioning
confidence: 95%
“…Instead, the Puna Rhea supplements its diet with the herbaceous H. doellii and S. philippiana, both considered excellent natural forage, and with higher protein levels than Lycium spp. (Ulibarri 1979;Cuevas et al 2013). The Puna Rhea consumed a large variety of the plant species recorded in the study area, a behaviour corresponding to a generalist foraging strategy (Recher 1990).…”
Section: Discussionmentioning
confidence: 99%
“…However, there were different periods when this species selectively consumed both shrubs (Adesmia sp.) and herbaceous species (G. pumila, H. doellii and S. philippiana), which are characterised by their high protein content (Cuevas et al 2013). In this sense the selection of food resources in terms of their nutritional value is a behaviour that the Puna Rhea shares with northern populations of the Lesser Rhea (Puig et al 2013).…”
Section: Discussionmentioning
confidence: 99%